Current models and practices of economic and environmental evaluation for sustainable network-level pavement management - Torres-Machi, Cristina; Chamorro, Alondra; Yepes, Víctor; Pellicer, Eugenio (Revista de la Construcción. Journal of Construction, 2014)
Ground transportation infrastructures, particularly road infrastructure, are essential for economic and social development. The quality level that the user perceives is mainly determined by the pavement condition. More than 400 billion dollars are invested globally each year in pavement construction and maintenance; these tasks increase by 10% the environmental impact generated by vehicle operation. Therefore, a sustainable approach should be incorporated in the assessment of preservation alternatives that consider technical, economic, environmental, political and institutional aspects in an integrated manner over their life-cycle. The purpose of the present research is to examine the models and practices for the economic and environmental evaluation of pavement assets, in order to analyze the advantages and limitations of the current state of the practice and identify the opportunities to improve their sustainable management. One of the main limitations identified is the lack of models that consider the economic and environmental aspects integrally. A need for models which consider the impact on users in work zones, as well as the use of new technologies and recycled materials that are more respectful of the environment, has been detected.